Relapsing Malaria: A Case Report of Primaquine Resistance - Christopher Dijanic; Jillian Nickerson; Sunita Shakya; Amanda Dijanic; Marilyn Fabbri (Case Reports in Infectious Diseases)
Primaquine (an 8-aminoquinoline malarial therapy) is the only FDA-approved therapy to treat the hypnozoite stage of P. vivax. We think of relapse occurring because of parasitic resistance or poor compliance secondary to drug toxicities. However, in patients with repeated treatment failure, we must consider CYP-450 mutations affecting drug metabolism as an important cause of relapse. A 47-year-old man who travelled to a jungle in Venezuela was diagnosed with P. falciparum and P. vivax in July 2015. He was treated with seven rounds of primaquine-based therapy in the following year, all resulted in relapse without further exposure to endemic areas. On his eighth presentation, he was found to have CYP-4502D6 mutation that affected the metabolism and activation of primaquine. Thereafter, he was treated without relapse. Primaquine efficacy depends on many factors. Understanding the mechanism responsible for malaria relapse is paramount for successful treatment and reduction in morbidity and mortality. This case illustrates the importance of considering cytochrome mutations that affect drug efficacy in cases of relapsing malaria.